Behavior of Bare, Cr3C2-20NiCr, and NiCrAlY coated Fe-Ni Based Superalloy Under Hot Corrosion in a 75 wt.% Na2SO4 + 25wt.% NaCl film at 9000C - Septianissa, Selly; Chandrasari, Ayu Zahra (GoAcademica Research & Publishing, 2024)
The main aim of this research is to assess the resistance to hot corrosion of untreated Fe-Ni-based superalloys compared to those coated with Cr3C2-20NiCr and NiCrAlY. These superalloys are strengthened through precipitation with ɣ’ Ni3(Al, Ti) and further fortified using high-velocity oxy-fuel (HVOF) thermal spray coating. The evaluation is performed under harsh conditions consisting at a temperature of 900°C for a duration of 25 cycles in a mixture containing 75 wt.% Na2SO4 and 25 wt.% NaCl. An optical microscope (OM) is utilized to determine the coating thickness of the coated specimens. Corrosion kinetics are evaluated by measuring changes in mass at the conclusion of each cycle during the investigation of hot corrosion. Furthermore, X-ray diffraction (XRD), energy dispersive spectroscopy (EDS), and scanning electron microscopy (SEM) are employed to investigate the chemical composition, ascertain phases, and scrutinize the surface morphology of the corrosion products. The findings reveal that the Fe-Ni superalloy, coated with precipitation-strengthened layers, demonstrates enhanced resistance to hot corrosion compared to the uncoated substrates, as evidenced by reduced weight gain per unit area. The coated substrates are enveloped by protective oxide layers consisting of chromium, nickel, aluminum, and their respective spinels, effectively shielding the substrate surfaces. In contrast, The superalloy without coating, which underwent precipitation hardening within the substrate, showed instances of microspalling and sputtering of the oxide scale. Findings suggested that both Cr3C2-20NiCr and NiCrAlY coatings substantially improved resistance against hot corrosion. Noteworthy was the superior protective efficacy of the NiCrAlY coating over the Cr3C2-20NiCr layer, attributed to the development of protective oxide scales containing Cr2O3 and NiCr2O4.